High Mortality During the Second Wave of the Coronavirus Disease 2019 (COVID-19) Pandemic in Uganda: Experience From a National Referral COVID-19 Treatment Unit - Bongomin, Felix; Fleischer, Brian; Olum, Ronald; Natukunda, Barbra; Kiguli, Sarah; Byakika-Kibwika, Pauline; Baruch Baluku, Joseph; Nakwagala, Frederick Nelson (Open Forum Infectious Diseases, 2021)
We evaluated clinical outcomes of patients hospitalized with coronavirus disease 2019 (COVID-19) in the second wave of the pandemic in a national COVID-19 treatment unit (CTU) in Uganda. Methods. We conducted a retrospective cohort study of COVID-19 patients hospitalized at the Mulago National Referral Hospital CTU between May 1 and July 11, 2021. We performed Kaplan-Meier analysis to evaluate all-cause in-hospital mortality. Results. Of the 477 participants, 247 (52%) were female, 15 (3%) had received at least 1 dose of the COVID-19 vaccine, and 223 (46%) had at least 1 comorbidity. The median age was 52 (interquartile range, 41–65) years. More than 80% of the patients presented with severe (19%, n = 91) or critical (66%, n = 315) COVID-19 illness. Overall, 174 (37%) patients died. Predictors of all-cause in-hospital mortality were as follows; age ≥50 years (adjusted odds ratio [aOR], 1.9; 95% confidence interval [CI], 1.2–3.2; P = .011), oxygen saturation at admission of ≥92% (aOR, 0.97; 95% CI, 0.91–0.95; P < .001), and admission pulse rate of ≥100 beats per minute (aOR, 1.01; 95% CI, 1.00–1.02; P = .042). The risk of death was 1.4-fold higher in female participants compared with their male counterparts (hazards ratio, 1.4; 95% CI, 1.0–2.0; P = .025). Conclusions. In this cohort, where the majority of the patients presented with severe or critical illness, more than one third of the patients hospitalized with COVID-19 at a national CTU died of the illness.
Keywords: COVID-19; Mortality; High-dependency unit; Second wave; Uganda